2012
DOI: 10.1063/1.4768959
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a laminar electron flow for 300 GHz high-power pulsed gyrotron

Abstract: This paper describes the design of a triode magnetron injection gun for use in a 200 kW, 300 GHz gyrotron. As power and frequency increase, the performance of the gyrotron becomes quite sensitive to the quality of the electron beam. Formation of a laminar electron flow is essential for the realization of a high quality beam with a small velocity spread. In this study, a new method is developed for a quantitative evaluation of the laminarity and is applied to optimize the electrode design. The laminarity depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…3(b)). As shown in the figure, α-values of electrons on the outer trajectory are always smaller than those of inner ones throughout the K-A region [5]. Here, it is found that the differences in α-values are produced by the differences in the parallel velocities (β // ).…”
Section: -1-4673-4717-4/13/$3100 ©2013 Ieeementioning
confidence: 57%
“…3(b)). As shown in the figure, α-values of electrons on the outer trajectory are always smaller than those of inner ones throughout the K-A region [5]. Here, it is found that the differences in α-values are produced by the differences in the parallel velocities (β // ).…”
Section: -1-4673-4717-4/13/$3100 ©2013 Ieeementioning
confidence: 57%
“…The electrode configurations were optimized by forming laminar electron trajectories, which resulted in a substantial reduction in the spread, Da, of the pitch factor (a) of the electron beam at the cavity entrance. 9,10 As a result, Da decreased from more than 30% in Gyrotron FU CW GII to 7% in Gyrotron FU CW GIII. 2,7 An inner mode converter composed of a Vlasov launcher 11 tunable and rotatable.…”
Section: Gyrotron Fu Cw Giiimentioning
confidence: 99%
“…The electrons are emitted from cathode and helically travel around the z-axis toward the cavity region. In [14], two Busch's theorem [12]- [15] is applied to estimate the parameters of a specified electron trajectory, and given as   …”
Section: Theoretical and Numerical Studymentioning
confidence: 99%